Fusion of gamma scintigraphic and magnetic resonance images improves the anatomical delineation of radiotracer for the assessment of gastrointestinal transit - Yeong, C.H.; Abdullah, B.J.; Ng, K.H.; Chung, L.Y.; Goh, K.L.; Perkins, A.C. (Lippincott, Williams & Wilkins, 2013)
Objectives: This paper describes the use of gamma scintigraphic and magnetic resonance (MR) fusion images for improving the anatomical delineation of orally administered radiotracers used in gastrointestinal (GI) transit investigations. Methods: Ten healthy volunteers ingested enteric-coated gelatin capsules containing 4.4Â±1.1 MBq 153SmCl3-labelled resin. Four external body markers containing 153Sm and Gd-DTPA were placed on the left and right lower costal margins and iliac crests of each volunteer. Anterior and posterior planar images were acquired hourly for 9 h, followed by a final single photon emission computed tomography (SPECT) image and subsequent T1-weighted images using a 1.5 T MR system. Coronal scintigraphic images were fused with MR images and assessed for diagnostic information. Results: The fused images revealed a combination of the tissue and organ anatomy with an overlay of the distribution of the tracer. Compared with conventional scintigraphic imaging alone, SPECT-MR fused images improved the localization of spatial and temporal movements of the radiotracer throughout the GI tract. Conclusion: Fusion of SPECT and MR images in conjunction with sequential scintigraphic images improved the assessment of segmental GI transit. These have the potential to provide more accurate diagnostic results and are visually powerful images that would have more widespread acceptance by nonspecialists.